Exploring EFL teachers’ English language proficiency: Lessons from Indonesia - Wulyani, Anik Nunuk; Elgort, Irina; Coxhead, Averil (Indonesian Journal of Applied Linguistics, 2019)
This paper reports on a study looking at the reading and writing proficiency and vocabulary knowledge of Indonesian EFL teachers, the relationship between proficiency and years of service, and the teachers’ own perceptions of their proficiency in English. Three proficiency tests (Vocabulary Levels Test/VLT, Reading and Writing Tests), questionnaire, and interview were used to collect data. The results point to mixed levels of English language proficiency, negative correlations between years of service and vocabulary, reading and writing test results, and that teachers themselves had difficulties in judging their own English language proficiency. Factors that inhibit the capacity of teachers to focus on their English proficiency are presented. Limitations of the study as well as implications for EFL teachers’ professional development (PD) and future research are also discussed.